INNOVATIVE ACTIVITIES OF INDUSTRIAL ENTERPRISES INFLUENCING FACTORS (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article analyzes the factors affecting the activities of industrial enterprises. Innovation is a decisive component for the success and stability of industrial enterprises.This allows companies to stay ahead of competitors, adapt to changing market conditions and meet changing customer expectations. However, there are several factors that facilitate or hinder the innovative activities of industrial enterprises. Below you can get some information about these factors